The mixed economy societies with private initiative in Colombia (2020)
This essay is intended to describe the regulations governing the creation and development of the mixed economi enterprises in Colombia. Stablishment, operation, reform of corporate bylaw, (at both the national and stale leve) and liquidation, will be the main aspects examined in this compositions. We Will indicate the main characteristics of the mixed - economi enterprises as well as the role that these companies play in meeting the goals set in the country’s economic development plan. We will also anlize the advantanges and disadvantages that the private and mixted-aconomy enterprises represent to the system. These advantyes and disad vanteges also dependo on the Parcent participation rate provied by the gourment to these organizations. This essay was created in order to conclude if companies created with 100% private equity coold ever become mexed- economy enterprises in Colombia.